Enhancing Intercultural Competence through Integrated English Teaching with Ethnic Narratives for Chinese Vocational Students in a Digital Context - Fan, Yanxia (Pacific International Journal, 2024)
In view of the increasingly intertwined and international situation, it is particularly important to cultivate students’ cross-cultural skills. The study primarily focused on innovative strategies to cultivate these capabilities in the Chinese vocational context. Within vocational training, learners will receive a high level of ESL support, including a curriculum enriched with ethnic stories, and digital resources and platforms. Stories of all ethnic groups, their narratives, traditions, and the manifestations of their cultures, have an important role to play in the realm of English language education; teachers can and should use these stories to deepen the students’ understanding of cultural issues, thus promoting a diverse context to nurture the feelings of empathy, respect, and the ability to communicate across cultures. Digital tools such as multimedia tools, e-platforms, and storytelling tools can provide students with authentic opportunities to interact with ethnic narratives to respond to their cultural exploration and communication in the digital environment. Results of case studies conducted at Chinese vocational universities illustrate the effective teaching methodologies, including project-based learning, integration of competitive tasks with class work, and cooperation that integrates students into groups to study various cultural perspectives presented in ethnic stories. The present study also explores implications for pedagogical practices, advocating improved teacher preparation in cross-cultural communication and digital literacy, as well as cross-disciplinary collaborations among language teachers and cultural studies scholars, and language and cultural policies for including and accommodating diverse languages and cultures in education contexts. Educators, through the incorporation of ethnic stories into English language instruction and digital assistance, enable vocational learners to excel in a globalized environment where skills in intercultural communication are becoming crucial.